IDENTIFIKASI PENYEBAB TURUNNYA KETERTARIKAN CALON PESERTA DIDIK UNTUK MENEMPUH PENDIDIKAN DI MI AL-FURQ'ON - Endang Sri Wahyuni; Ismail Marzuki (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
In this investigation, we will find out the cause of prospective students' interest in studying at MI Al-Furqon Srowo Sidayu. This study uses descriptive qualitative research with interview research methods using interview questionnaires which can Refer to obtain the expected research result. The subjects in this study were residents around MI Al-Furqon Srowo Sidayu, children who did not attend school at MI Al-Furqon Srowo Sidayu, and kindergarten-level children in groups A dan groups B. The result of this study indicates that the cause of the lack of interest of prospective students to study at MI Al-Furqon Stowo Sidayu occurs due to 2 factors, namely internal factors, and external factors. Internal factors are causes that exist within the individual (institution), and external factors are causes that come from outside the individual (institution). 67% of the cause of the lack of interest of prospective students to study at MI Al-Furqon are caused by internal school factors, 33% occur due to school external factors and the biggest external factor is following friends.